Development of an anti-acne cream based on natural oils: Investigation of the effect of ingredients on rheology, texture properties, and physical stability - Mohabbat Gandomkar; Ardalan Pasdaran; Gholamhosein Yousefi (Shiraz University of Medical Sciences, 2023)
Acne vulgaris is a very common skin problem. Cutibacterium acnes (formerly Propionibacterium acnes), a common skin organism, is most notably recognized for its role in acne vulgaris. Standard oral and topical treatments have significant side effects including skin irritation, indigestion, and also, cause resistance to antibiotics. In current study, o/w creams based on ostrich and sesame fixed oils containing Mentha piperita, Origanum vulgare and Lavandula officinallis essential oils as active ingredients were developed. The results showed that using Cetomacrogol 1000/Cetostearyl alcohol (CSA) as emulsifier/co-emulsifier could produce stable o/w creams containing 10-30 % w/w of fixed oils with various consistencies. Long-term (room temperature/24 months), accelerated (40 °C/ three months), thermocycling (-10 °C for 24h/40 °C for 24 hr) and centrifuge test (3000 rpm, 30 min at 50 °C) studies all showed the very high physical stability of the formulations. The rheological studies showed the shear-thinning thixotropic behavior of creams and Ostwald equation as the best model describing behavior of the creams. Texture analysis showed the significant effects of ingredients on creams hardness and adhesiveness having a reasonable correlation to spreadability test results. The results showed that aqueous and oil soluble thickening agents had the highest effect on rheological and texture parameters. Finally, the optimum cream was standardized using gas chromatography equipped to mass detector (GC-MS).